Optimization of Tooth Profile Modification and Backlash Analysis of Multi-tooth Mesh Cycloid Transmission - Zhang, Liyong; Xu, Wentao; Zhi, Yanfeng; Hou, Nai; Li, Hongwei; Wang, Chanlu; Li, Tongjie; Zhang, Yu; Zhang, Hanlin; Chen, Jijie (Manufacturing Technology Journal, 2024)
Cycloid gear drive is widely used in robot cycloid planetary reducer, and the transmission accuracy is the key property of the reducer. The standard cycloid transmission is a multi-tooth mesh. The modification method has attracted extensive attention as one of the important parameters of the cycloid drive. The influence of the isometric and shifting modification of the cycloid gear on the cycloid transmission backlash was analysed according to the characteristics of the multi-tooth mesh and the profile equation of the modified cycloid gear in this study. Combined with the backlash analysis, a multi-objective optimization mathematical model of cycloid gear modification parameters was established to ensure the backlash and strength of the reducer. The study showed that the modification combination mode and parameters were obtained under different application conditions, thus providing a certain reference for the modification parameter design of cycloid transmission.
Keywords: Cycloid transmission; Tooth profile; Modification; Backlash; Optimization